2005
DOI: 10.1210/en.2005-0298
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Regulation of the Age-Related Decline in Testosterone Biosynthesis

Abstract: The age-related decline in testosterone biosynthesis in testicular Leydig cells has been well documented, but the mechanisms involved in the decline are not clear. Recent studies have described a cyclooxygenase-2 (COX2)-dependent tonic inhibition of Leydig cell steroidogenesis and expression of the steroidogenic acute regulatory protein (StAR). The present study was conducted to determine whether COX2 protein increases with age in rat Leydig cells and whether COX2 plays a role in the age-related decline in tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 36 publications
(34 reference statements)
4
90
1
Order By: Relevance
“…Previous studies have reported that StAR protein expression and testosterone production were decreased in aged Leydig cells. [9][10][11]33 No studies on the linkage between autophagy and testosterone production have been reported, although Taneike et al 34 reported decreased autophagic activity in aged heart tissue, and Zhang et al 29 reported low autophagic activity in aged smooth muscles of the corpus cavernosum. Our study showed that the autophagic activity could affect StAR protein We attributed the linkage between lower testosterone levels and autophagic deficiency in aged Leydig cells to intracellular ROS accumulation generated from dysfunctional or aged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that StAR protein expression and testosterone production were decreased in aged Leydig cells. [9][10][11]33 No studies on the linkage between autophagy and testosterone production have been reported, although Taneike et al 34 reported decreased autophagic activity in aged heart tissue, and Zhang et al 29 reported low autophagic activity in aged smooth muscles of the corpus cavernosum. Our study showed that the autophagic activity could affect StAR protein We attributed the linkage between lower testosterone levels and autophagic deficiency in aged Leydig cells to intracellular ROS accumulation generated from dysfunctional or aged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the apparent critical function of an "acute" regulatory protein in steroidogenesis, it is of interest that expression of both StarD1/StAR and PBR/TSPO is downregulated in the adrenal and Leydig cells of aging rats [422][423][424][425][426]. For example, studies from this laboratory have shown an 80% reduction in StarD1/StAR protein expression of nonstimulated Leydig cells prepared from old Sprague-Dawley rats suggesting that the impaired testosterone production that occurs during aging may involve attenuated StAR expression [422].…”
Section: Aging and P38 Subfamily Of Map Kinasesmentioning
confidence: 99%
“…By immunohistochemistry, we found only positive PTGS2 immunostaining in Leydig cells of the reproductively active seasonal breeder Syrian hamster (Frungieri et al 2006). However, other authors have been able to detect PTGS2 expression in testes and Leydig cells from rats, mice and even humans using different experimental techniques such as RT-PCR, real-time RT-PCR and western blot (O'Neill & Ford-Hutchinson 1993, Neeraja et al 2003, Wang et al 2005, Balaji et al 2007, Chen et al 2007, Winnall et al 2007. One plausible explanation for these discrepancies is that the levels of PTGS2 expression in normal testes of most species, including the men, may be too low to be detected by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, these early studies suggest that PGs may not be important for the functioning of the testis. However, several reports have shown that PTGS is up-regulated in testicular cancer (Hase et al 2003) and aging (Wang et al 2005), and that some PGs (i.e. PGD 2 , PGE 2 , PGF 2a ) participate in the regulation of testicular testosterone production (Saksena et al 1973, Kimball et al 1979, Didolkar et al 1981, Sawada et al 1994, Romanelli et al 1995, Gunnarsson et al 2004.…”
Section: Introductionmentioning
confidence: 99%